2009
DOI: 10.1073/pnas.0900349106
|View full text |Cite
|
Sign up to set email alerts
|

The primary signaling outputs of brassinosteroids are regulated by abscisic acid signaling

Abstract: Phytohormones have essential roles in coordinately regulating a large array of developmental processes. Studies have revealed that brassinosteroids (BRs) and abscisic acid (ABA) interact to regulate hundreds of expression in genes, governing many biological processes. However, whether their interaction is through modification or intersection of their primary signaling cascades, or by independent or parallel pathways remains a big mystery. Using biochemical and molecular markers of BR signaling and ABA biosynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
216
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(227 citation statements)
references
References 50 publications
(62 reference statements)
10
216
1
Order By: Relevance
“…These apparently conflicting data might be explained considering that BRs perform diverse functions by sharing signaling pathways with other phytohormones. For example, it has been demonstrated that ABA inhibits plant growth by suppressing BR signaling downstream of BR receptor (Zhang et al 2009). An antagonistic interaction has been also evidenced between BRs and gibberellins, since the GA repressor DELLA directly interacts with BZR1 to inhibit its DNA binding and thus transcription activity in controlling photomorphogenesis (Sun et al 2010;Li et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These apparently conflicting data might be explained considering that BRs perform diverse functions by sharing signaling pathways with other phytohormones. For example, it has been demonstrated that ABA inhibits plant growth by suppressing BR signaling downstream of BR receptor (Zhang et al 2009). An antagonistic interaction has been also evidenced between BRs and gibberellins, since the GA repressor DELLA directly interacts with BZR1 to inhibit its DNA binding and thus transcription activity in controlling photomorphogenesis (Sun et al 2010;Li et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple overlaps in the gene sets regulated by BR and GA, and in the biological effects of these two hormones, and the BR-regulated transcriptional activity of BZR1 and BES1 is known to be required for proper GA responses in skotomorphogenic seedlings 1,3 . In addition, similar to GAs, BRs play negative roles in ABA-inhibited early seedling development [14][15][16] , and exogenous BR application or overexpression of BR biosynthetic DWF4 can overcome the low seed germination phenotype of GAdefective mutants 43 . Furthermore, central negative regulators of GA signalling, DELLA proteins, could directly inhibit the transcriptional activity of BES1 and BZR1, and BR activity was required for GA-mediated cell elongation 1,3 .…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous BR application rescued the low germination phenotype of GA-related mutants and BR-defective mutants are hypersensitive to ABA during early seedling development and stomatal closure [14][15][16] . Furthermore, the biologically active BR (brassinolide and castasterone) and BR biosynthetic gene expression were greatly increased during seed growth and germination of Pisum sativum (pea) 17 .…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In addition to the genetic interactions of ABA signaling with ethylene, gibberellins, and brassinosteroids signal transduction in embryonic and early postembryonic development (Beaudoin et al, 2000;Gazzarrini et al, 2004;Ghassemian et al, 2000;Zhang et al, 2009), novel roles of ABA signaling during pathogen infection and following defense responses against biotic stresses have been suggested (Asselbergh et al, 2008;Cao et al, 2011;Fujita et al, 2006;Ton et al, 2009). Jasmonic acid (JA) and salicylic acid (SA) are two major plant hormones regulating plant biotic stress signal transduction.…”
Section: Interaction Of Aba Signaling With Biotic Stress Response Patmentioning
confidence: 99%